2009
DOI: 10.17705/1jais.00208
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption and Use of IT Artifacts: A New Interaction-Centric Model for the Study of User-Artifact Relationships

Abstract: Research ArticleSameh Al-Natour The University of British Columbia sameh@interchange.ubc.ca Izak BenbasatThe University of British Columbia benbasat@sauder.ubc.caThe question of why a user adopts an information technology (IT) artifact has received ample research attention in the past few decades. Although recent adoption research has focused on investigating some of the relational and experiential aspects associated with adopting and using IT artifacts, the theories utilized have been static in nature. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 73 publications
4
88
0
2
Order By: Relevance
“…Par ailleurs, en mobilisant la valeur perçue, le cadre théorique proposé permet de se décentrer de la prise de décision de l'individu dans un contexte multicanal et multiforme pour comprendre les effets de complémentarité des canaux et des offres en phase de consommation (Oppewal, Tojib et Louvieris, 2013). La mobilisation de la valeur perçue permet également d'adopter une approche centrée sur l'utilisateur (Banker et Kauffman, 2004 ;Alter, 2007 ;Al-Natour et Benbasat, 2009), d'intégrer une dimension affective (Sun et Zhang 2006 ;Al-Natour et Benbasat, 2009) et de privilégier une approche holiste pour appréhender l'expérience utilisateur (Hassenzahl et Tractinksy, 2006 ;Deng et al, 2010).…”
Section: Iv1 Contributions Théoriques Et Managérialesunclassified
See 1 more Smart Citation
“…Par ailleurs, en mobilisant la valeur perçue, le cadre théorique proposé permet de se décentrer de la prise de décision de l'individu dans un contexte multicanal et multiforme pour comprendre les effets de complémentarité des canaux et des offres en phase de consommation (Oppewal, Tojib et Louvieris, 2013). La mobilisation de la valeur perçue permet également d'adopter une approche centrée sur l'utilisateur (Banker et Kauffman, 2004 ;Alter, 2007 ;Al-Natour et Benbasat, 2009), d'intégrer une dimension affective (Sun et Zhang 2006 ;Al-Natour et Benbasat, 2009) et de privilégier une approche holiste pour appréhender l'expérience utilisateur (Hassenzahl et Tractinksy, 2006 ;Deng et al, 2010).…”
Section: Iv1 Contributions Théoriques Et Managérialesunclassified
“…Dans un contexte où les entreprises sont de plus en plus nombreuses à proposer à leurs clients un portefeuille de produits et de canaux, les chercheurs doivent adapter leurs modèles en privilégiant une perspective à deux dimensions combinant conjointement canaux et offres. Ensuite, si le monde académique a pour l'instant largement investi la question du choix des canaux ou des offres (Simon et Kadiyali, 2007 ;Ansari, Mela et Neslin, 2008), celle de leur usage complémentaire reste à l'heure actuelle moins explorée (Bendana et Rowe, 2003 ;Al-Natour et Benbasat, 2009 ;Oppewal, Tojib et Louvieris, 2013) (Avery et al, 2012 ;Collin-Lachaud et Vanheems, 2016). C'est le cas de la presse où les problématiques de diffusion peuvent être rapprochées des problématiques de distribution .…”
Section: Introductionunclassified
“…Another type of two-way communication we have advocated involves viewing the interaction between the user and the technology as a relationship that changes over time based on the events and outcomes that occur when the two parties interact and how the user assesses these interactions not only at a single point in time, but over repeated interactions (Al-Natour and Benbasat, 2009). This is different than the research which showed that over time the user assesses a technology based on different criteria, such as putting less emphasis on ease-of-use over time.…”
Section: Nature Of Evaluation and Constructs Of Interestmentioning
confidence: 99%
“…Some has dealt with the concept of service (Cenfetelli, Benbasat and Al-Natour, 2006) where we showed that the company has to provide both the content of service (such as order tracking), as well the traditional HCI goal of delivering this content via the best possible interface. In summary, I believe that we now need to focus on two sets of key variables: those dealing with the interface between a person (customer) and a technology, and those that describe the quality of the reciprocal relationship or the quality of the communication between a customer and another entity, the online company.Another type of two-way communication we have advocated involves viewing the interaction between the user and the technology as a relationship that changes over time based on the events and outcomes that occur when the two parties interact and how the user assesses these interactions not only at a single point in time, but over repeated interactions (Al-Natour and Benbasat, 2009). This is different than the research which showed that over time the user assesses a technology based on different criteria, such as putting less emphasis on ease-of-use over time.…”
mentioning
confidence: 99%
“…The common thread throughout this research is that the focus has primarily been on (1) the intentional choices and behaviors of individuals directed towards an information system or technology in a (2) mandatory context or work-related setting. Very little research has begun to explore the flipside of these assumptions and look at the (1) non-intentional interactions individuals have with information systems and technologies in (2) voluntary contexts and non work-related environments. To address these gaps this study focuses on voluntary-use information systems.…”
Section: Introductionmentioning
confidence: 99%